Od teatru okrucieństwa do Grand Guignolu. Śmierć w kinie Andrzeja Żuławskiego - Jacek Nowakowski (Przestrzenie Teorii)
This essay shows the motif of death in the film works of Andrzej Żuławski in the perspective of the theatre of horror. Starting with Trzecia część nocy (The Third Part of the Night) (1971) until his late work Szamanka (The Shaman Woman) (1996), this film work is shown as evolving from the patronage of the conception of art of Antonin Artaud, serving the transformation of man up to its peculiar autoparody, which is closer to Grand Guignol. The author proves that escalation of cruelty in his works gradually loses its artistic pretext (justification) ceases to be artistically justified (no longer find artistic justification).